Effects of in utero exposure to valproate or levetiracetam on the seizures and newborn histopathology of genetic absence epilepsy rats. (17th April 2022) - Can Kantarci, Berk; Sanli, Ahmet; Gavas, Seyhmus; Toplu, Aylin; Nur Turgan Asik, Zehra; Tugce Cilingir-Kaya, Ozlem; Gulcebi Idrizoglu, Medine; Ercan, Feriha; Onat, Filiz
Highlights: Valproate treatment before and during pregnancy prolongs the time to give birth. In utero valproate and levetiracetam do not show antiepileptogenic effects. Levetiracetam exposure in utero interferes with alveolar development. Levetiracetam adversely affects the kidney following foetal exposure. Abstract: Valproate (VPA) and levetiracetam (LEV), the two broad spectrum antiseizure drugs with antiabsence effects were previously tested for their antiepileptogenic effects when administered in the early postnatal period and revealed possible modification of the epileptogenic process though the effect being not persistent. The aim of this study was to investigate the effects of in utero exposure to these drugs on the absence epilepsy seizures of Genetic Absence Epilepsy Rats from Strasbourg (GAERS) rats on electroencephalogram (EEG) which are characterised by bilateral, symmetrical, and synchronized spike-and-wave discharges (SWDs). Considering LEV was proposed as a safer drug of choice in pregnancy, its effects on the newborn histopathology of GAERS was also investigated. Adult female GAERS were randomly grouped as VPA-(400 mg/kg/day), LEV- (100 mg/kg/day), and saline-treated. The drugs were injected into the animals intraperitoneally starting before pregnancy until parturition. The lungs, kidneys, and brains of the LEV-exposed newborns were evaluated histologically to be compared with unexposed naïve Wistar and GAERS newborns. Rest of the VPA-, LEV-, and saline-exposed offsprings were taken for EEG recordings on postnatal day 90. VPA or LEV did not show significant effect on mean cumulative duration and mean number of SWDs on EEG. The lungs of the LEV-exposed offsprings showed thickened alveolar epithelium in most regions, suggesting incomplete development of the alveoli. The renal examination revealed dilated Bowman's spaces in some renal corpuscles, which may be interpreted as a deleterious effect of LEV on the kidney. In addition, brain examination of LEV- and saline-exposed groups revealed irregularities in cortical thickness compared to Wistar control group. Lack of significant difference on SWD parameters may indicate that the mechanism responsible for the antiepileptogenic effects of VPA and LEV may not be operating in the prenatal period. The detrimental effect of LEV exposure observed in our study on the lungs and the kidneys of the newborns should be investigated by further studies with advanced molecular and biochemical techniques.